The effect of compensation factors on job satisfaction among employees in Syarikat Air Johor (SAJ) Holdings Sdn Bhd, Mersing, Johor / Nurliana Zulkeflee and Mohamad Syahir Razak - Zulkeflee, Nurliana; Razak, Mohamad Syahir (Faculty of Business and Management, 2016)
Job satisfaction is the important thing that each organization should take consideration seriously. This is because satisfaction of employees can lead directly outcome and organization performance. This study is aiming to see job satisfaction among employees in Syarikat Air Johor (SAJ) Holdings Sdn Bhd Mersing, Johor. As job satisfaction can lead to better performance and outcome, thus employees will satisfy the customer and also giving a good image of organization to the public. This study consists of the analysis on the analysis on the potential factors that can affect job satisfaction. Pearson correlation analysis is used to determine the strength of relationship between independent variable and dependent variable while regression analysis used to determine the most independent variable factor that influence dependent variable. The researcher getting data for this research study through questionnaire that distributed to 86 selected employees by using simple random sampling method. The result from the research study shows that three out of four independent variables has significant relationship toward job satisfaction. The variables are pay, recognition and meaningful work, while promotion opportunity does not have significant relationship towards job satisfaction. In addition, it also found that the most influence factor that affects job satisfaction is pay.